Short interbirth interval and adverse pregnancy outcomes: a Bayesian network approachAJOG Global Reports at a Glance - Silvina L. Heisecke, DVM; Hebe Campaña, MSc, PhD; María R. Santos, BSc, PhD; Jorge S. López Camelo, MSc, PhD; Mónica Rittler, MD, PhD (Elsevier, 2024)
Background: Interbirth interval (IBI), the time between consecutive births, has been tied to perinatal outcomes. Objective: To analyze adverse perinatal events following short IBI in a large South American sample. Study design: Observational, retrospective, hospital-based study including malformed and nonmalformed live- and stillbirths. Outcomes were preterm birth (PTB), low birth weight (LBW), and specific birth defects. Logistic regressions were used to evaluate the risk of selected variables for short IBI and for adverse outcomes after short IBI, adjusting by confounders. Bayesian networks exhibited relationships among short IBI, outcomes, and variables. Results: Short IBI rate was 2%-3%. Maternal age and a previous abortion were the main confounders. A significant high risk for short IBI was found in mothers ≤19 years while mothers ≥30 were at low risk, mediated by a previous abortion. The risk of short IBI, adjusted by confounders, was significant for LBW but not for PTB. An unadjusted risk of short IBI was observed for gastroschisis, which disappeared after adjusting for confounders. Maternal age ≤19 and previous abortion were directly related with gastroschisis; the relationship between gastroschisis and short IBI occurred through any of these two variables. A direct relationship between gastroschisis and maternal age ≥30 was observed. Conclusions: Only young mothers were directly related with short IBI. In older mothers, a short IBI mainly occurred after a previous abortion. Short IBI was a risk factor only for LBW. The PTB and gastroschisis relationship with short IBI was indirect, mediated by young maternal age and/or a previous abortion.